2021
DOI: 10.1080/01402382.2020.1852374
|View full text |Cite
|
Sign up to set email alerts
|

Can't buy me votes? Campaign spending and the outcome of direct democratic votes

Abstract: Recent American studies that investigate the influence of money on the outcome of direct democratic votes find campaign spending effective for both supporters and challengers. Taking advantage of Switzerland's far-reaching experience with direct legislation, this article tests the role of money in a 'harder' context, where government plays an active role in direct democratic processes. It assesses the impact of campaign spending on 323 federal votes, and on a subset of 60 votes, offering finer-grained cantonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…In other words, cantonal voting behavior is nested within cantons and specific votes, but the latter two are independent from each other (Gelman and Hill 2007, 289ff. ; also Jaquet et al 2022 for a similar approach). The main independent variable of interest, federal government membership, is also located at level 2 since it pertains to cantons.…”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations
“…In other words, cantonal voting behavior is nested within cantons and specific votes, but the latter two are independent from each other (Gelman and Hill 2007, 289ff. ; also Jaquet et al 2022 for a similar approach). The main independent variable of interest, federal government membership, is also located at level 2 since it pertains to cantons.…”
Section: Methodsmentioning
confidence: 86%
“…The main independent variable of interest, federal government membership, is also located at level 2 since it pertains to cantons. Multilevel models offer a compromise between complete pooling (which ignores variation between cantons and votes) and no pooling (which ignores it through separate models for each canton or vote) (Jaquet et al 2022, 253 and 279). I model random intercepts at the level of cantons and votes because basic levels of turnout, for instance, could be inherently different across cantons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the results of empirical studies on the impact of campaign spending on public referenda remain inconclusive (i.e., some studies have found campaign spending against a ballot more effective than spending in favour, while other recent analyses argue that spending is similarly effective for both sides; see De Figueiredo et al, 2011;Garrett & Gerber, 2001;Jaquet et al, 2022;Lupia & Matsusaka, 2004), the size of campaigners' budgets does matter. As might be expected, the higher a campaigner's budget, the more resources and power they have to influence voters, including through advertising (Broder, 2001;De Figueiredo et al, 2011;Matsusaka, 2004).…”
Section: Referendum Campaign Budgets and Advertising Expenditures In ...mentioning
confidence: 99%
“…Direct democracy, together with federalism and consociationalism, is a central cornerstone of the Swiss political system (Vatter, 2020). The Swiss constitution provides for different elements of direct citizen participation, allowing for the creation, abolition, or modification of legislative norms: popular initiatives, optional, and mandatory referenda (Jaquet et al, 2022;Serdült, 2010). Since 1848, the Swiss electorate has voted on a total of 676 proposals at the national level (Swissvotes, 2022).…”
Section: Equalization Vs Normalization and Direct Democracy: The Swis...mentioning
confidence: 99%